Analisis Pengaruh Brand Ambassador Terhadap Keputusan Pembelian Scarlett Whitening di Kabupaten Magelang (Studi Kasus pada Song Joong-ki, Twice, dan Dinda Hauw) Analysis of The Influence of The Ambassador Brand Scarlett Whitening Purchase Decision in Mag - Khania, Arum; Supriyadi, Muh (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
Scarlett Whitening is a body care product from Indonesia with Brand Ambassadors Song Joong-ki, Twice, and Dinda Hauw. This research was conducted to find out how influential Brand Ambassadors Song Joong-ki, Twice, and Dinda Hauw are in consumer purchasing decisions for Scarlett Whitening products. This research uses quantitative methods, data collection was carried out by distributing questionnaires to 100 respondents in Magelang Regency who used Scarlett Whitening products with brand ambassadors Joong-ki, Twice, and Dinda Hauw. The data analysis method used in this research is the multiple linear regression test, t test, coefficient of determination test, and F test. Based on the results of hypothesis testing, especially the t test and multiple linear regression, it is concluded that all the independent variables (visibility, credibility, attraction, and power ) has a significant influence on purchasing decisions for Scarlett Whitening in Magelang Regency. Likewise, the results of the F test show that all independent variables (visibility, credibility, attraction, and power) have a significant effect on purchasing decisions for Scarlett Whitening in Magelang Regency.